Glacial-interglacial and millennial-scale changes in terrigenous supply and ocean circulation in the western South Atlantic - Igor M. Venancio; João M. Ballalai; Douglas V.O. Lessa; Thiago S. Figueiredo; Raissa Tayt-Sohn; Marianna C. Motta; Aurélio F. Silva; Nathalia O. de Lima; Beatriz C.O.D.S.S. da Silva; Rut Díaz; Manuel Moreira; Anderson G. de Almeida; et al. (Evolving Earth)
Oceanic circulation changes play a fundamental role in shaping past climate variability in northeastern Brazil, influencing precipitation patterns and sediment transport on glacial-interglacial and millennial timescales. However, the extent to which these processes vary across different water depths and their geochemical imprints in marine sediments remain poorly constrained. Here, we present multiproxy geochemical records from three sediment cores in the Sergipe Basin, located off northeastern Brazil, spanning the last 45,000 years. Variations in Fe/Ca, Zr/Rb, TOC, CaCO3, and sulfur content reveal distinct glacial-interglacial shifts, with enhanced terrigenous input and reduced carbonate deposition during glacials, likely linked to lower sea level and changes in ocean circulation. Millennial-scale fluctuations in sulfur and Zr/Rb suggest variations in deep-water ventilation and bottom-current speed. These results provide new insights into the regional paleoceanographic evolution of the western South Atlantic and reinforce mechanisms driving sedimentary responses to past climate variability.